2016
DOI: 10.1515/jpem-2015-0235
|View full text |Cite
|
Sign up to set email alerts
|

The relation of urinary bisphenol A with kisspeptin in girls diagnosed with central precocious puberty and premature thelarche

Abstract: The BPA levels did not differentiate between groups and it seems that the exposed amount of BPA in daily life did not affect kisspeptin levels in girls with CPP and PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
20
0
2
Order By: Relevance
“…A total of 11 studies [20,[34][35][36][37][38][39][40][41][42][43] were included, comprising 316 CPP patients and 251 controls. Figure 1 outlines study selection process in a PRISMA flowchart.…”
Section: Systematic Review and Summary Of Evidencementioning
confidence: 99%
“…A total of 11 studies [20,[34][35][36][37][38][39][40][41][42][43] were included, comprising 316 CPP patients and 251 controls. Figure 1 outlines study selection process in a PRISMA flowchart.…”
Section: Systematic Review and Summary Of Evidencementioning
confidence: 99%
“…Serum or urinary BPA concentrations were significantly associated with premature thelarche [39,51], precocious puberty [32,37,44,50], and earlier pubertal development [48]. However, other studies have reported no significant relationship [29-31,33-36,38,40-43,47] or later onset of puberty or menarche [45,46,49]. Although most previous studies for BPA and pubertal milestones were limited by cross-sectional or case-control study designs, 6 longitudinal studies have been reported [33,41,45,47-49].…”
Section: Bisphenol Amentioning
confidence: 99%
“…As consequence, kisspeptin administration in immature rodents and primates was able to induce precocious activation of the gonadotropic axis and precocious pubertal development [23][24][25]. Additionally, kisspeptin levels are higher in girls with central precocious puberty [26,27]. In gonadal juvenile male monkeys, however, the continued kisspeptin administration decreases the LH levels, consequently leading to the assumption that kisspeptin secretion is pulsatile, and the continuous stimulation may induce receptor desensitization [28,29].…”
Section: Function In Puberty and Reproductive Systemmentioning
confidence: 99%